TANGGUNG JAWAB DEBITUR ATAS PENGALIHAN OBYEK JAMINAN FIDUSIA PERJANJIAN PEMBIAYAAN MULTIGUNA KEPADA PIHAK KETIGA - Liva Wadillah (2022)
The increasing material needs of the community have directly encouraged the existence of Financing Institutions as alternative financing facilities (services) that help people who need fast funds with an installment payment system (credit). Where there is a legal event, namely a financing agreement involving the lender (creditor) and loan recipient (debtor), as a condition of legal validity. If the debtor is negligent or fails to pay off his debt, a guarantee is needed as one of the objects within his control, which is called the object of fiduciary security. Law Number 42 of 1999 concerning Fiduciary Guarantees (UUJF) as a regulation regarding Fiduciary, one of the references on which the research is based is contained in Article 23 (2) of the UUJF "The Fiduciary Giver is prohibited from transferring, mortgaging, or leasing to other parties the object that becomes the object of the Fiduciary Guarantee which is not an object of inventory, except with prior written approval from the Fiduciary Recipient." The purpose of the research is to determine the debtor's responsibility and legal protection to creditors for the transfer of the object of the Fiduciary Guarantee of multipurpose financing agreements to third parties. In this study, the author uses a normative juridical research method, namely by conducting an assessment of the Court's Decision, and the Legislation as the primary legal material associated with textbooks and legal journals as secondary data support. The results of the study show that debtors need to be responsible for breaking promises (wanprestasi) in multipurpose financing agreements based on the provisions of Article 1243 of the Civil Code, and unlawful acts (PMH) that they have committed based on the provisions of Article 1365 of the Civil Code by fulfilling compensation. As for the legal protection of creditors, it can be done through risk mitigation based on Article 26 of the POJK, as well as through registration and execution of fiduciary guarantees. The author's suggestion is that there is a need for legal certainty regarding the responsibility of the debtor.